Design of a Website-Based Battuta University Employee Payroll System - Nur Alisya, Siti; Harahap, Baginda; Wayahdi, M. Rhifky (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
Everything in this world is bound to change, including technological advancements. Technology will never stop developing. The exchange of data and information is now very fast, even in less than a second. At Battuta University, in processing employee salaries, they still use manual calculations and use the Ms. Excel application. This can cause errors in calculating employee salaries and the process of printing pay slips and employee payroll reports that take a long time. In solving this problem, the author designs a website-based employee payroll application. In designing the application, the author uses a system development methodology, namely the waterfall and qualitative methods, with the application program language made in PHP and MySQL database. The results of this design produce a computerized application program which will be used to process web-based employee salaries at Battuta University and it is hoped that the university will find it easier to input data, compile payroll reports faster and more efficiently.